Michael Loy, Connecting communities in archaic Greece: exploring economic and political networks through data modelling. British School at Athens studies in Greek antiquity. - Canevaro, Mirko (Journal of Greek Archaeology, 2025)
Michael Loy’s monograph is an innovative and intriguing contribution to the growing body of work using computational methods in archaeology. It takes advantage of the vast – and often unwieldy – datasets produced by more than a century of excavations in Greece, especially by the foreign schools, analysed by Loy through Social Network Analysis and spatial modelling to make sense of economic and political interactions across the Aegean in the seventh and sixth centuries BC.